Mechanisms of Replication Protein A-dependent R-loop resolution by the human DNA repair helicase, HelQ. - Betts, Hannah (2024)
To mitigate the devastating effects of unrepaired DNA damage, prokaryotes and eukaryotes alike have an abundance of mechanisms to correct potentially genome-destabilising insults as and when they arise. DNA repair helicases play an important role in coordinating this repair.